Heart is for Love: Cognitive Salience and Visual Metonymies in Comics. Issue 1 (26th June 2018) - Kowalewski, Hubert
Abstract : This article explores the role of conceptual proximity as a parameter of salience in visual metonymies. The study discusses visual metonymy as a type of conceptual metonymy understood as a way of referring to one concept (the target) via another concept (the vehicle; cf. Lakoff and Johnson 1980, Radden and Kövecses 1999). The vehicle and the target are connected through a contiguity relation salient in a given context. A formal framework is developed for describing such salient contiguities and the key hypothesis is that the salience effect is determined largely by the conceptual distance between the target and the vehicle within a network of available contiguity relations. For example, when a musical note (the vehicle) is used in graphic narrative to refer metonymically to a melody (the target), the note is selected for the vehicle, because there is low conceptual distance between the two concepts.